초심자 권총사격시 생체지표변화에 관한 연구: 경찰간부후보생 사격특성을 중심으로 - 신충화 (한국해양경찰학회보, 11(2), 2021)
본 연구는 정식 사격교육을 받기 전의 경찰 간부후보생들의 사격시 심박변동에 근거한 생체지표를 측정, 분석하여 신임경찰관 사격능력향상을 위한 교육 개선 방안을 제시하는 것에 관한 것이다. 연구대상은 경찰간부후보생 남녀 21명을 대상으로 하였으며, 가슴에 부착하는 생체정보 소형측정기기를 사용하였다. 측정환경은 38구경 리볼버 권총과 9mm탄을 사용하는 K5 피스톨 권총을 사용하여 실시간으로 생체정보를 측정하면서 정해진 절차에 맞추어 사격을 실시하였다. 측정결과 성별, 체중별, 연령별, 사격방식, 총기종류별로 달라지는 사격자의 생체지표 요인별 변화와 사격단계 별로 달라지는 연속적인 변화 또한 확인할 수 있었다. 결론적으로 현재의 사격교육 개선에 있어서는 리볼버와 피스톨의 각각의 특성에 맞는 구분된 교육이 필요하며, 사격의 지속으로 인한 피로감이나 스트레스를 개선할 수 있는 훈련도 필요하다는 결론을 얻었다. 본 연구가 그러한 사격교육 개선에 있어서 기초자료로서 사용되기를 기대한다. This study is about measuring and analyzing biomarkers based on heart rate fluctuations during shooting of police officer candidates before receiving formal shooting training, and presenting educational improvement plans to improve the shooting ability of new police officers. The subjects of this study were 21 male and female police officer candidates, and a small biometric information measuring device attached to the chest was used. As for the measurement environment, a 38-caliber revolver pistol and a K5 pistol pistol using 9mm ammunition were used to measure biometric information in real time, while shooting according to the prescribed procedure. As a result of the measurement, it was also possible to confirm changes by factors of the shooter's biomarkers, which vary by gender, weight, age, shooting method, and type of firearm, and continuous changes that vary by shooting stage. In conclusion, it was concluded that in order to improve the current shooting education, separate education suitable for each characteristic of revolver and pistol is necessary, and training to improve fatigue or stress caused by continuous shooting is also necessary. It is expected that this study will be used as basic data in improving such shooting education. KCI Citation Count: 0